Ozone Improves the Aromatic Fingerprint of White Grapes. Issue 1 (December 2017) - Río Segade, Susana; Vilanova, Mar; Giacosa, Simone; Perrone, Irene; Chitarra, Walter; Pollon, Matteo; Torchio, Fabrizio; Boccacci, Paolo; Gambino, Giorgio; Gerbi, Vincenzo; Rolle, Luca
Abstract Ozone, a powerful oxidative stressor, has been recently used in wine industry as sanitizing agent to reduce spoilage microflora on grapes. In this study, we evaluated ozone-induced metabolic and molecular responses during postharvest grape dehydration. Ozone increased the contents of total volatile organic compounds (VOCs), which have a great impact on the organoleptic properties of grapes and wines. Among terpenes, responsible for floral and fruity aroma, linalool, geraniol and nerol were the major aromatic markers of Moscato bianco grapes. They were significantly affected by the long-term ozone treatment, increasing their concentration in the last phases of dehydration (>20% weight loss). At molecular level, our results demonstrated that both postharvest dehydration and ozone exposure induce the biosynthesis of monoterpenes via methylerythritol phosphate (MEP) pathway and of aldehydes from lipoxygenase-hydroperoxide lyase (LOX-HPL) pathway. Therefore, transcriptional changes occurred and promoted the over-production of many important volatile compounds for the quality of white grapes.